Allocentrism and consumer ethnocentrism: the effects of social identity on purchase intention - Huang, Y.; Phau, Ian; Lin, Chad; Chung, H.; Lin, K. (Society for Personality Research, 2008)
This article examines the effects of allocentrism and consumer ethnocentrism (CET) on purchase intentions for domestic versus imported products focusing on the current phenomenon of the “Korean Wave” in Taiwan. Research based on data collected from 433 mall intercept interviews in Taiwan indicates that there is a strong positive relationship between allocentrism toward parents and CET. However, a significantly negative relationship between allocentrism toward friends and CET was also established. The findings also revealed that friends in-group’s attitude toward Korean TV dramas has a mediating effect of allocentrism toward friends on CET and CET on the purchase intention of Korean products. One contribution of the study is that CET played a mediating relationship between allocentrism toward parents and friends and purchase intention. This ethnocentric effect was attributed to parental and friends in-groups which played a significant role in reducing/enhancing the impact of inter-group discrimination, making national identification a less obvious and important social category. These have significant implications for domestic and foreign marketers, especially in the global market place.